No longer left on the shelf: How Savour! Made yet-to-be-sold F&B products an attractive proposition - CHIYACHANTANA, Chiraphol N. (Institutional Knowledge at Singapore Management University, 2023)
Singapore-based tech social enterprise Savour! seeks to make procurement smoother and more productive by linking up suppliers like merchants with less commercially-oriented procurers such as non-profit organisations and school clubs via its B2B e-commerce platform and app. It originally focused on food products that were blemished or had a limited shelf life, but has since expanded its range of products and services to include corporate gifts, office supplies, and event rental services. Both merchants and procurers deal with each other via the digital platform or app, which offers discounts of varying percentage depending on how soon the products would expire. Savour! was set up by Katrina Lee and a group of like-minded youths when they were all still undergraduates. They had met when participating in a green business pitch competition aimed at achieving environmental sustainability. Lee had been spurred to found the company as a result of her temporary job stints during which she had witnessed large amounts of food being wasted. Lee has plans to take the company beyond Singapore but has not yet decided to which country in the region it wishes to next expand. In the meantime, Savour! is seeking more funding to raise its merchant and customer acquisition rate, and intensify its product development. The case is designed for undergraduate, postgraduate, and executive education students of finance, entrepreneurship, digital business, and sustainability in business. Students who have successfully examined the case should be able to appreciate the commonality and disparities between social enterprises and conventional businesses, grasp how social enterprises maintain commercial viability while pursuing their social mission, and discern that businesses can be disrupted.